Pengaruh Inovasi Produk, Citra Merek, dan Digital Marketing Terhadap Keputusan Pembelian Produk Scarlett Whitening di Kota Batam - Martha Sarma Ulina; Winda Evyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the extent to which product innovation, brand image, and digital marketing influence the purchasing decisions of Scarlett Whitening consumers in the city of Batam. The subjects of this study are individuals who have used Scarlett Whitening products in Batam City in 2025. The population size could not be determined precisely, so the sample size was determined using the Lemeshow formula, with a total of 100 respondents selected through purposive sampling. The analysis method used is multiple linear regression, supported by a series of tests, including data quality tests, classical assumption tests, and hypothesis tests. The analysis results show that product innovation has an influence of 27.7%, brand image of 28.4%, and digital marketing of 26.5% on consumer purchasing decisions. Meanwhile, the coefficient of determination (R²) value indicates that simultaneously, these three variables can explain 28.9% of the variation in purchasing decisions. Furthermore, the results of the t-test and F-test prove that product innovation, brand image, and digital marketing have a significant effect, both partially and simultaneously, on the purchasing decisions for Scarlett Whitening products in Batam City. Keywords: Product Innovation,Brand Image, Digital Marketing, Purchase Decision.